2021
DOI: 10.1021/acscatal.1c03149
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Construction of Tertiary/Secondary Carbon–Phosphorus Bonds via Bifunctional Phosphonium Salt Catalyzed 1,6-Addition

Abstract: The carbon–phosphorus bond engenders distinctive physicochemical properties and has significant applications in chemical science. Herein, we disclose an efficient and practical catalytic protocol for the asymmetric synthesis of remote C–P bonds by a synergistic strategy of stabilizing the P-nucleophile by a chiral phosphonium salt catalyst together with activating the extended π-system by a side group, thus leading to a cascaded 1,6-addition/aromatization reaction. This protocol provides straightforward and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…In connection to our previous findings, [16c–g] we also believed that the hydrogen‐bonding interactions as well as ion‐pair activation contributed significantly to the asymmetric induction for this cascade reaction. In this context, we carried out studies to demonstrate its importance.…”
Section: Resultssupporting
confidence: 83%
“…In connection to our previous findings, [16c–g] we also believed that the hydrogen‐bonding interactions as well as ion‐pair activation contributed significantly to the asymmetric induction for this cascade reaction. In this context, we carried out studies to demonstrate its importance.…”
Section: Resultssupporting
confidence: 83%
“…Of note, the X‐ray structure of the similar catalyst P9 was obtained (CCDC 1909436), [27] and the ESP of catalyst P9 was also calculated, both of which suggested that H‐bonding and ion‐pairing interactions might be existed as the key factors for the chiral induction. Considering these mechanistic results and our previous studies on the PPS‐catalyzed asymmetric formation of C−P bond, [26c,d] the plausible stereo‐control models were proposed in Figure 5D. In view of X‐ray crystallographic data of nitro‐activated oxa[5]helicene substrate ( 1 b ), [27] we proposed that the stereoselectivity of the C−P bond formation primarily originated from the steric hindrance, particularly which came from the catalyst‐bounded both phosphorus oxide and nitro‐activated oxa[5]helicene via hydrogen‐bonding and ion‐pairing interactions.…”
Section: Resultsmentioning
confidence: 52%
“…Shortly after, Wang and co‐workers further applied this catalytic system to a highly enantioselective 1,6‐conjugate addition/aromatization reaction of phosphine oxides with cyano‐substituted para ‐quinone methides [55] . As shown in Scheme 15A, PPS catalyst P13 with multiple hydrogen‐bonding donors could provided the desired chiral tertiary C−P stereocentralized molecules in high yields with satisfactory enantioselectivities.…”
Section: Application Of Pps Catalysts In Asymmetric Synthesismentioning
confidence: 99%